Creativity and Innovations in Retail Banking- A Comparative Analysis of Financial Products Offered by ICICI and HDFC Bank - Sofat, Rajni; Hiro, Preeti (Indian Journal of Marketing, 2007)
The dynamic nature of the present entrepreneurial organizations and its interaction with the present competitive business environment poses various critical issues in all the industries irrespective of their current market status. In order to gain competitive edge and postpone the maturing of the products and the industry, the entrepreneurs need to evolve constantly. Evolution thrives on creativity and Innovation. As it has been rightly said, "Creative thinking ability facilitates the ability to realize innovations." Innovations are indispensable but are not easy to adopt, further inducing these innovations into the business value chain may not be simple as the implications of the upgraded and advanced tools offered by any entrepreneur or corporate requires compatibility with customer’s expectations and in turn an appropriate customer’s reaction to sustain. Innovation is a multi-dimensional and multi disciplinary concept. Rapid technological innovations have led to the emergence of several new and creative financial products in retail banking. The creativity and innovation in the retail banking is mainly attributable to the rapid advances in information technology, financial sector reforms, growth of the Indian economy, increasing per capita income and several micro level demand and supply related factors. The different innovative products and services offered by ICICI and HDFC bank are: wide variety of Deposit products, Demat Services, ATMs, Cards, Corporate Internet Banking, Kid’s Advantage Account, Cash Management Services, etc. Thus, these banks provide convenience, efficiency, and accessibility to their customers and are gaining more and more importance